Research progress and present situation of integrated medical and nursing ward rounds (医护一体化查房模式的研究进展及现状) - LI Qianqian (李倩倩); YE Yun (叶云) (Association of Integrative Nursing, 2023)
This paper reviewed the literature related to the mode of integrated medical and nursing ward rounds, and summarized the concept of integrated medical and nursing ward rounds, the implementation method, the application status in clinical nursing, the problems existing in the implementation process and the countermeasures, so as to provide reference for the improvement and popularization of integrated medical and nursing ward rounds in the clinical setting. (本文对医护一体化查房模式的相关文献进行归纳和总结, 从医护一体化的概念、医护一体化查房模式的实施方法、在临床护理的应用现状、实施过程中存在的问题及应对措施几个方面进行综述, 以期为临床医护一体化查房工作模式的完善和推广使用提供参考依据。)